Vitamin D Biofortification of Pork May Offer a Food-Based Strategy to Increase Vitamin D Intakes in the UK Population - Neill, Holly R.; Gill, Chris I. R.; McDonald, Emma J.; McRoberts, W. Colin; Pourshahidi, L. Kirsty (Frontiers in Nutrition, 2021)
Hypovitaminosis D is prevalent worldwide, with many populations failing to achieve the recommended nutrient intake (RNI) for vitamin D (10-20µg/day). Owing to low vitamin D intakes, limited exposure to ultraviolet-B (UVB) induced dermal synthesis, lack of mandatory fortification and poor uptake in supplement advice, additional food-based strategies are warranted to enable the UK population to achieve optimal vitamin D intakes, thus reducing musculoskeletal risks or suboptimal immune functioning. The aims of the current study were to 1) determine any changes to vitamin D intake and status over a 9-year period, and 2) apply dietary modeling to predict the impact of vitamin D biofortification of pork and pork products on population intakes. Data from the UK National Diet and Nutrition Survey (Year 1-9; 2008/09-2016/17) were analyzed to explore nationally representative mean vitamin D intakes and 25-hydroxyvitamin D (25(OH)D) concentrations (n=13,350). Four theoretical dietary scenarios of vitamin D pork biofortification were computed (vitamin D content +50/100/150/200% vs standard). Vitamin D intake in the UK population has not changed significantly from 2008 to 2017 and in 2016/17, across all age groups, 13.2% were considered deficient (25(OH)D <25 nmol/L). Theoretically, increasing vitamin D concentrations in biofortified pork by 50, 100, 150 and 200%, would increase vitamin population D intake by 4.9, 10.1, 15.0 and 19.8% respectively. When specifically considering the impact on gender and age, based on the last scenario, a greater relative change was observed in males (22.6%) vs. females (17.8%). The greatest relative change was observed amongst 11-18 year olds (25.2%). Vitamin D intakes have remained stable in the UK for almost a decade, confirming that strategies are urgently required to help the population achieve the RNI for vitamin D. Biofortification of pork meat provides a proof of concept, demonstrating that animal-based strategies may offer an important contribution to help to improve the vitamin D intakes of the UK population, particularly adolescents.